Preparation of Chitosan-Fe3O4 Nanoparticles by Ex-Situ Co-Precipitation Using Tripolyphosphate / Sulfate as Crosslinker and Characterization Using XRD - Ika Oktavia Wulandari; Akhmad Sabarudin; Djoko Herry Santjojo (Natural B, Journal of Health and Environmental Sciences, 2016)
Magnetic nanoparticles of Fe3O4 was synthesized in this research by using ex-situ copresipitation method followed by surface modification with crosslinked chitosan along with trypolyphospate (TPP) and sulfate crosslinking agents. The Fe3O4 materials were formed from FeCl2.H2O and FeCl3.6H2O with 1:2 ratio under alkaline condition. Surface modification processes were conducted by mixing chitosan solution with purified Fe3O4 yielding a ferrogel solution as a product. Here, the crosslinker agents, TPP and sulfate, were added to the mixture to make a crosslinking compounds. In these processes, the chitosan-Fe3O4 crystallite size were affected by composition ratio and crosslinking time which will be proven by using x-ray diffraction (XRD) and modified Debye-Scherrer methods. The results showed that, on highest ratios between chitosan and Fe3O4 as well as TPP/sulfate crosslinker, gave the smallest size of crystallite of chitosan-Fe3O4. Furthermore, the more time of crosslinking process caused crystallite size of chitosan-Fe3O4 became much smaller.